2017
DOI: 10.3390/ijgi6040125
|View full text |Cite
|
Sign up to set email alerts
|

Generating Up-to-Date and Detailed Land Use and Land Cover Maps Using OpenStreetMap and GlobeLand30

Abstract: Abstract:With the opening up of the Landsat archive, global high resolution land cover maps have begun to appear. However, they often have only a small number of high level land cover classes and they are static products, corresponding to a particular period of time, e.g., the GlobeLand30 (GL30) map for 2010. The OpenStreetMap (OSM), in contrast, consists of a very detailed, dynamically updated, spatial database of mapped features from around the world, but it suffers from incomplete coverage, and layers of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 23 publications
1
52
0
Order By: Relevance
“…The accuracy of artificial surfaces was tested in eight areas around the world, which ranged from 79% to 97%, showing improvements when compared with CORINE Land Cover [54] and the FROM-GLC product [55]. A more recent validation of GlobeLand30 for Dar Es Salaam, Tanzania, and Kathmandu, Nepal, yielded overall accuracies of 61% and 54%, respectively [56]. Other independent validations of GlobeLand30 include comparisons with authoritative products in Italy [57], Germany [58], Iran [59], and water bodies in Scandinavian countries [60], with agreements of greater than 78%.…”
Section: Globeland30mentioning
confidence: 99%
“…The accuracy of artificial surfaces was tested in eight areas around the world, which ranged from 79% to 97%, showing improvements when compared with CORINE Land Cover [54] and the FROM-GLC product [55]. A more recent validation of GlobeLand30 for Dar Es Salaam, Tanzania, and Kathmandu, Nepal, yielded overall accuracies of 61% and 54%, respectively [56]. Other independent validations of GlobeLand30 include comparisons with authoritative products in Italy [57], Germany [58], Iran [59], and water bodies in Scandinavian countries [60], with agreements of greater than 78%.…”
Section: Globeland30mentioning
confidence: 99%
“…for Africa (see Fig. 2) where accuracies from regional case studies were also reported to be lower (Fonte et al, 2017;See et al, 2017). Nonetheless, despite greater challenges for a consistent land cover classification at a global level and its inherent complexity to compete with regional and continental datasets, global datasets are able to provide us with a more comprehensive picture over the entire globe by also providing information for areas that are currently underrepresented by regional and continental datasets, e.g.…”
Section: Evaluation Of Results and Sources Of Uncertaintymentioning
confidence: 99%
“…Regional accuracy assessments of Globeland30 yielded lower accuracies, e.g. for Dar Es Salaam (Tanzania) and Kathmandu (Nepal) accuracies were 61 and 54 %, respectively (Fonte et al, 2017), while in Kenya it was found to be 56-64 % . Accuracies for Italy (Brovelli et al, 2015), Germany (Jokar Arsanjani et al, 2016a), and Iran (Jokar Arsanjani et al, 2016b) were greater than 78 % .…”
Section: Empirical Datamentioning
confidence: 99%
“…Hecht et al, 2013;Fan et al, 2014;Brovelli et al, 2016b), land use (see e.g. Jokar Arsanjani et al, 2015b;Fonte et al, 2017) and points of interest (see e.g. Girres and Touya, 2010;Jackson et al, 2013).…”
Section: Openstreetmap Quality Assessmentmentioning
confidence: 99%